HARGA DIRI DAN KONFORMITAS TERHADAP KELOMPOK DENGAN PERILAKU MINUM MINUMAN BERALKOHOL PADA REMAJA - - cipto; Joko Kuncoro (Proyeksi: Jurnal Psikologi, 2010)
The major purpose of this research is to find the relations between self esteem and conformity with dringking behavior. This study also try to find the contribution of each independen variabel to the dependen variabel. The sample of this research are 52 teenages who watch rock music concert at kudus . The result of this study using multiple regression technique show that there was significan correlation between between self esteem and conformity with dringking behavior with R = 0,125; p = 0,000 (p < 0,01; significan), F = 21,386 dan p = 0,000. Statistical analysis also shows that there was positive significan correlation between self esteem and drinkin behavior with rxy= - 0,313; p = 0,000 (p<0,01).  The relation between conformity and drinking behavior is positive significa with rxy = 0,397 ;             p= 0,000 (p<0,01). This is mean tha all hypothesis are proven or accepted. The final conclusion of this study is there is significan relationship between self esteem and  conformity  with drinking behavior among teenage at kudus.  Keyword : drinking behavior, self esteem, conformity